2021
DOI: 10.24114/jp.v5i2.28857
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Pembelajaran Pjok Pada Masa Pandemi Covid-19 Di Sd Negeri Se-Kecamatan Percut Sei Tuan Kabupaten Deli Serdang

Abstract: Penelitian ini merupakan penelitian deskriptif kuantitatif dengan pendekatan One Shot Case Study dan metode survei. Penelitian ini bertujuan untuk mengetahui dan menganalisis implementasi pembelajaran PJOK pada masa pandemi Covid-19 di SD Negeri se-Kecamatan Percut Sei Tuan Kabupaten Deli Serdang. Sampel yang digunakan dalam penelitian ini yaitu guru PJOK yang sudah mendapatkan sertifikasi di SD Negeri se-Kecamatan Percut Sei Tuan Kabupaten Deli Serdang yang berjumlah 38 sekolah dengan 47 guru PJOK. Penelitian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Pendidikan jasmani mengandung makna bahwa mata pelajaran ini menggunakan aktivitas jasmani sebagai media untuk mencapai tujuan aktivitas pembelajaran yang direncanakan, yang bertujuan untuk meningkatkan kebugaran jasmani individu (Putra, 2020)…”
Section: Pendahuluanunclassified
“…Pendidikan jasmani mengandung makna bahwa mata pelajaran ini menggunakan aktivitas jasmani sebagai media untuk mencapai tujuan aktivitas pembelajaran yang direncanakan, yang bertujuan untuk meningkatkan kebugaran jasmani individu (Putra, 2020)…”
Section: Pendahuluanunclassified
“…Another study found that the only part of the learning was following the lesson plans (Putra, 2020). 100% of the assessments were based on assignments and exams, 83.3% of teachers said that online learning assessments were inadequate, and 50% of the obstacles in learning Physical Health and Sports Education online are difficulties accessing the internet.…”
Section: Introductionmentioning
confidence: 99%
“…This scarcity is characterized by the study of physical education learning in non-disabled children. Previous research on DL on physical education for elementary school (SD) students (Putra, 2020), junior high school (SMP) (Simbolon et al, 2021), and high school (SMA) (Sulaksono & Wibowo, 2021) has showed several things, including students feel encouraged to study remotely without adequate facilities and infrastructure at home; and students also do not have a culture of DL because so far, the learning system has been done face-to-face/offline. Students are used to being in the school environment to interact with their friends, play and have fun and face-to-face with teachers, in addition, the school is closed for too long so the children are bored, a factor that causes students to lose their social soul.…”
Section: Introductionmentioning
confidence: 99%